SENSORY STIMULATION THERAPY BY LISTENING TO MUSIC IN THE ELDERLY - Ninik Murtiyani; Kusuma Wijaya Ridi Putra; Riesmiyatiningdyah Riesmiyatiningdyah (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Group Activity Therapy given to the elderly using the Sound Sensory Stimulation method by listening to music for the elderly at UPT PMKS Mojopahit Mojokerto is a form of community service in the form of Activity Therapy activities that are expected to reduce social interaction problems that occur in the elderly. This activity was carried out on April 16, 2022 at UPT PMKS Mojopahit Mojokerto. The target of this activity is all the elderly who are in UPT PMKS Mojopahit Mojokerto. Before the activity was carried out, the implementers of this community service activity made preparations approximately 3 weeks before the implementation of the activity in order to prepare the implementation method, determine the type of therapy to be carried out up to the application of licensing for the implementation of the activity to the parties concerned. As a form of evaluation, the activity was attended by 25 elderly people, the participants participated in the activity very enthusiastically, the Group Activity Therapy activity went well, on time, and smoothly.